An Improved Hardy-Rellich Inequality with Optimal Constant - Yang Qiao-Hua; Xiao Ying-Xiong (Journal of Inequalities and Applications, 2009)
We show that a Hardy-Rellich inequality with optimal constants on a bounded domain can be refined by adding remainder terms. The procedure is based on decomposition into spherical harmonics.